THE EFFECT OK5R STRATEGY ON STUDENTS' ACHIEVEMENT IN READING COMPREHENSION AT THE SMA N 15 TAKENGON BINAAN NENGGERI ANTARA - Muhammad Hasyimsyah Batubara; Delfia Herwanis; Dharma (Jurnal As-Salam, 2020)
Reading comprehension is a skill that must be possessed by students so that they can take the main ideas of the text correctly. Based on researchers' observations, almost all students at SMA N 15 Takengon Binaan Nenggeri Antara experienced difficulty reading comprehension skills. The researcher applied (OK5R Strategy) to determine its effect on students' reading comprehension of descriptive texts. This research uses quantitative methods with the type of experimental research and data collection using observation and tests. The sample used in this study was X IPA3 as an experimental class and X IPS2 as a control class, each consisting of 20 students. The findings on using the OK5R strategy positively affect the learning achievement of students' reading comprehension in grade X SMA N 15 Takengon Binaan Nenggeri Antara. Based on these results, teachers can practice this strategy in the teaching and learning process.